Iron ion and sulfasalazine-loaded polydopamine nanoparticles for Fenton reaction and glutathione peroxidase 4 inactivation for enhanced cancer ferrotherapy. (June 2022) - Zhu, Xiaokang; Chen, Qifang; Xie, Li; Chen, Wenjie; Jiang, Yang; Song, Erqun; Song, Yang
Abstract: Ferroptosis shows promising potential in tumor treatment; however, factors that compromise the efficiency of the Fenton catalyst have limited its therapeutic effectiveness. We developed a polydopamine-based nanoplatform constructed with ferric ion and sulfasalazine-loaded nanoparticles (Fe(III)PP@SAS NPs) for dual-functional ferrotherapy strategy of "sword and shield" through enhanced Fenton reaction and inactivation of glutathione peroxidase 4 (GPX4), respectively. Both the Fenton reaction-based hydroxyl radical ( · OH) production and sulfasalazine-driven GPX4 inhibition induced ferroptotic cell death, thus achieving synergistic cancer therapy. Near-infrared light irradiation and acidic tumor microenvironment enhanced the release of ferric ions and sulfasalazine from the Fe(III)PP@SAS NPs. In addition, the released iron ions underwent valence state change due to Fenton reaction and thus provided a supplementary T1-weighted signal for in situ visualization of the tumor based on magnetic resonance imaging. The Fe(III)PP@SAS NPs exhibited high pro-ferroptosis performance by utilizing · OH radicals as a "sword" to attack cancer cells and the GPX4 inhibitor to break down the "shield" of cancer cells, thus showing potential for cancer treatment. Statement of significance: Several strategies of cancer therapy based on ferroptosis have emerged in recent years, which have provided new insights into designing materials for therapeutic applications. The antitumor efficacy of ferroptosis is, however, still unsatisfactory, mainly because of insufficient intracellular pro-ferroptotic stimuli. In the current study, we report a multifunctional theranostic nanoplatform, namely Fe(III)PP@SAS, with three-fold synergistic effect; this nanoplatform has excellent theranostic potential with multifunctional ferrotherapy. Graphical abstract: Image, graphical abstract